2018
DOI: 10.1007/s10654-018-0426-4
|View full text |Cite
|
Sign up to set email alerts
|

Body fatness, diabetes, physical activity and risk of kidney stones: a systematic review and meta-analysis of cohort studies

Abstract: We conducted a systematic review and meta-analysis to clarify the association between adiposity, diabetes, and physical activity and the risk of kidney stones. PubMed and Embase were searched up to April 22nd 2018 for relevant studies. Summary relative risks (RRs) and 95% confidence intervals (CIs) were calculated using random effects models. Thirteen cohort studies were included. The summary relative risk was 1.21 (95% CI 1.12–1.30, I2 = 76%, n = 8) per 5 unit increment in BMI, 1.16 (95% CI 1.12–1.19, I2 = 0%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
62
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(83 citation statements)
references
References 55 publications
(78 reference statements)
3
62
0
1
Order By: Relevance
“…For additional EJE references please see [197][198][199][200][201][202][203][204][205][206][207][208].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…For additional EJE references please see [197][198][199][200][201][202][203][204][205][206][207][208].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…[ 13 ] Risk factors including obesity, diabetes mellitus, hypertension and metabolic syndrome contribute to the KS formation. [ 14 , 15 ] A variety of managements for KS are available, such as acupuncture, herbal medicine, surgery, dietary supplementation, oral medicine, and extracorporeal shock wave lithotripsy (ESWL). A numerous studies have reported that ESWL can effectively treat patients with KS.…”
Section: Introductionmentioning
confidence: 99%
“…En el caso de la obesidad abdominal, varios estudios evidencian la relación de la adiposidad visceral aumentada y el desarrollo de enfermedades crónicas no transmisibles [11][12] . Un metaanálisis realizado por un grupo de investigadores europeos en el año 2017 mostró la asociación entre aumento de la obesidad abdominal, resistencia a insulina y riesgo de enfermedades renales 13 . Enfermedades que generan enormes gastos para los sistemas de salud y la sociedad 14 .…”
Section: Cita Introducciónunclassified